Glomerular Hematuria as a Predictor of Renal Prognosis in Malignant Hypertension Patients with Thrombotic Microangiopathy: A Propensity Score-Matched Analysis of a Biopsy-Based Cohort Study - Zhaocai Zhou; Wanxin Shi; Shengyou Yu; Jianwen Yu; Naya Huang; Zhong Zhong; Fengxian Huang; Wei Chen; Feng He; Jianbo Li (Kidney Diseases, 2024)
Introduction: Malignant hypertension (mHTN) is a hypertensive emergency. Thrombotic microangiopathy (TMA) is a widespread complication of mHTN. Few studies have evaluated whether glomerular hematuria provides prognostic information for renal dysfunction in patients with mHTN-associated TMA. Methods: This observational cohort study included 292 patients with mHTN-associated TMA based on renal biopsy. Propensity-score matching (PSM) analysis was conducted to adjust for clinical characteristics in a comparison between with and without glomerular hematuria. Cox regression was employed to identify risk factors for renal prognosis. Results: A total of 70 patients with glomerular hematuria were compared to 222 patients with non-glomerular hematuria. After PSM, 67 pairs of patients with mHTN-associated TMA were matched. Patients with glomerular hematuria exhibited lower serum albumin levels, higher 24-h proteinuria, and a higher prevalence of glomerular sclerosis than those with non-glomerular hematuria. Glomerular hematuria was independently associated with deteriorated renal function compared with non-glomerular hematuria (HR: 0.51; 95% CI: 0.29–0.89, p = 0.019). This association remained significant after PSM (HR: 0.51; 95% CI: 0.28–0.91, p = 0.022). Additionally, glomerular hematuria was independently associated with renal replacement therapy (RRT) (HR: 3.14; 95% CI: 2.06–5.66, p < 0.001). This difference remained significant after PSM comparison (HR: 2.41; 95% CI: 1.34–4.33, p = 0.003). Furthermore, despite intensive blood pressure control, patients with glomerular hematuria experienced a higher incidence of RRT and a poorer recovery in renal function, specifically a 25% reduction of creatinine levels, compared to patients with non-glomerular hematuria. Conclusion: Glomerular hematuria is significantly associated with an increased risk of adverse renal outcomes in patients with mHTN-associated TMA.